2016
DOI: 10.1108/bfj-12-2015-0460
|View full text |Cite
|
Sign up to set email alerts
|

Reducing waste of food left on plates

Abstract: Purpose Social marketing and other types of targeted behaviour change interventions should appeal to an individual’s personal values in order to improve their effectiveness. However, there is currently little understanding of what these values are in relation to food waste. The purpose of this paper is to identify the values underpinning the specific behaviour of plate waste created in a residential foodservice setting. Design/methodology/approach In semi-structured interviews (n=50) laddering techniques wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 37 publications
(38 reference statements)
5
58
1
1
Order By: Relevance
“…Williams et al (2012) reported that individuals with high environmental awareness were likely to waste less food. Furthermore, Mirosa et al (2016) related this fact to the personal value of universalism (care for the welfare of all and for nature), indicating that individuals who care for others and the environment are less likely to waste food. They also highlight the fact that people feel guilty when they waste food.…”
Section: Food Waste Drivers At School Canteens and Recommended Intervmentioning
confidence: 99%
See 2 more Smart Citations
“…Williams et al (2012) reported that individuals with high environmental awareness were likely to waste less food. Furthermore, Mirosa et al (2016) related this fact to the personal value of universalism (care for the welfare of all and for nature), indicating that individuals who care for others and the environment are less likely to waste food. They also highlight the fact that people feel guilty when they waste food.…”
Section: Food Waste Drivers At School Canteens and Recommended Intervmentioning
confidence: 99%
“…Table summarizes the abovementioned diverse categorized food waste drivers and a couple of examples of each together with the cited sources. (Cooke et al, 2011;Mirosa et al, 2016;Williams et al, 2012;Yoon & Kim, 2012) Operational reasons Procurement specifications Menu composition (Falasconi et al, 2015;Rodriguez Tadeo et al, 2014) Situational reasons Unpleasant canteen environment…”
Section: Food Waste Drivers At School Canteens and Recommended Intervmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoring was guided by answering two main questions: The first analysed actor is the consumer. Consumer interest is considered to be medium to high (score 4) because UK consumers different uses and purposes where some studies used it to understand consumers values behind either 'wasting' or 'not wasting' behaviours in a foodservice context (Mirosa et al 2016). In this research, the means-end chain analysis is used to identify products, services and system attributes that could support consumers to purchase, store, prepare and consume food efficiently so that food waste is minimised.…”
Section: Stakeholder Identification Methodologymentioning
confidence: 99%
“…Many studies underline the role of educational campaign to improve awareness and change behaviors, as example a study on nutritional education found that information education raise awareness and it shown a negative correlation with plate waste rates [12] and another study in South Korea shown that students who recognized the need for nutritional education were significantly lower and students' attitudes towards food waste reduction were negatively correlated with plate waste rate [13].…”
Section: Introductionmentioning
confidence: 99%